Comparative transmission of five viruses by Bemisia tabaci NW2 and MEAM1 - De Marchi, Bruno R. [UNESP]; Marubayashi, Julio M. [UNESP]; Favara, Gabriel M. [UNESP]; Yuki, Valdir A.; Watanabe, Luís Fernando M. [UNESP]; Barbosa, Leonardo F.; Pavan, Marcelo A. [UNESP]; Krause-Sakate, Renate [UNESP] (Springer Nature, 2017)
Bemisia tabaci is one of the most serious agricultral pests worldwide, causing severe damage mainly by transmitting plant viruses. B. tabaci is currently classified as a cryptic species complex. Within the complex, the invasive Middle East-Asia Minor 1 (MEAM1) species is the prevalent one in Brazil. However, there are also two indigenous species, New World 1 (NW1) and New World 2 (NW2), which have not been completely displaced by the exotic invasive species. The ability of the native species to transmit viruses is still unclear. In this study we have detected and identified begomoviruses present in NW1 and NW2 specimens collected in the field. Moreover, pure colonies of NW2 and MEAM1 were established and used for virus transmission assays. Sequences of begomoviruses detected in native whiteflies from the field suggest the presence of viruses typically associated with weeds. Similar to MEAM1, the NW2 species was able to transmit all the begomovirus, crinivirus and carlavirus isolates assessed and was shown to be a highly effective vector of Bean golden mosaic virus (BGMV) and Euphorbia yellow mosaic virus (EuYMV). Our results indicate that the NW2 indigenous species might play a relevant role in the transmission of economically important viruses like BGMV and in the maintainance of begomoviruses associated with weeds.
Keywords: Begomovirus; Biotype B; Carlavirus; Crinivirus; Middle East-Asia Minor 1; New World 2; Whitefly